Three new Hymedesmia Bowerbank, 1864 (Demospongiae, Poecilosclerida, Hymedesmiidae) from the Southeast Pacific (Peru and Chile) - Salani, Sula; Willenz, Philippe; Fernandez, Julio C.c.; Hajdu, Eduardo (Zootaxa, 2022)
Despite its 2000 km long shoreline, to date less than 50 sponge species have been reported from the entire Peruvian coast. A large collecting effort targeting marine sponges was undertaken between 2007 and 2009, yielding a comprehensive collection of nearly 900 samples, whose taxonomic study is underway. Three new species of Hymedesmiidae are presently described from the Peruvian coast, all belonging in Hymedesmia (Hymedesmia), one of which also found in Chile. Hymedesmia (H.) santarositae sp. nov., from Isla Santa Rosa (Paracas), is characterized by the presence of microstrongyles next to sigmas. Hymedesmia (H.) peruana sp. nov., from Isla Foca (Piura), is diagnosed by its three categories of acanthostyles, and single categories of tornotes and arcuate isochelae. Hymedesmia (H.) humboldti sp. nov., from Moquega and Arequipa regions in Peru, and Antofagasta and Atacama regions in Chile, is diagnosed by its two categories of acanthostyles, and single categories of (aniso)strongyles and arcuate isochelae, the latter abundant at the surface. An identification key for Hymedesmia spp. from the South-eastern Pacific, South-western Atlantic, the Sub-Antarctic and the Antarctic is provided.